Формування моделі житлового будівництва в місті - Титок, В. В. (Ways to Improve Construction Efficiency, 2013)
In the articles certain basic parameters of structure of housing building are in large town as complex control system, a mathematical model which represents the dynamics of development of building in him is offered.